ENGLISH PRESENTATION TRAINING FOR OFFICE MANAGEMENT STUDENTS AT POLITAMA SURAKARTA - Asri, Anindhiasti Ayu Kusuma; Purbasari, Dita Anggi (Digulis: Jurnal Pengabdian Pada Masyarakat, 2024)
Language is a fundamental tool for human interaction, and learning native and foreign languages is essential. As a global language, English is crucial in various fields, including business, science, and education. This community service aims to enhance Office Management students' presentation skills in English at Politama Surakarta. Observations revealed that students often lack confidence and hesitate to participate actively due to limited exposure to English-speaking environments. This community service activity employed lectures, discussions, QA sessions, and hands-on practice to address these challenges and develop students' speaking proficiency and self-confidence. The training was structured into three stages: introducing presentation techniques, teaching visual aid creation using tools like Canva, and providing guided practice sessions. The findings demonstrate significant improvements in students' confidence, organizational abilities, and presentation proficiency. Students reported a greater understanding of the material and active engagement during sessions. The results emphasize that integrating presentation techniques into EFL classes fosters an engaging and productive learning environment. By encouraging active participation, students enhance their speaking skills and develop critical thinking, teamwork, and organizational abilities essential for professional success.